In-hospital mortality analysis in patients with acute cardiovascular pathology and co-infection with COVID-19: a registry of one site. (3rd May 2023) - Lutay, I; Khomiakov, D; Irkin, O; Stepura, A; Bilyi, D; Parkhomenko, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Patients with cardiovascular pathology have a significantly higher risk of adverse events and death when complicated by concomitant COVID-19. The aim of this study was to analyze in-hospital mortality in pts with acute cardiovascular pathology (ACP) and a co-infection with COVID-19. 139 pts with ACP who were diagnosed with COVID-19 were examined. 69 (49.6%) pts had ACS (47 pts with AMI), 33 (23.7%) pts - hypertensive urgency, 24 (17.3%) pts - ADHF, 9 (6.5%) pts - tachysystolic paroxysm of atrial fibrillation, 2 (1.4%) pts - acute pulmonary embolism, and 2 (1.4%) pts - syncope. The average age was 67.9±12.7 y.o., 70 (50.4%) pts were male. Concomitant arterial hypertension was found in 87.1%, DM – 20.9%, CHF - 30.9%, COPD – 9.4% of pts, history of AMI – 20.1% and ischemic stroke – 9.4% of pts. In 79 (56.8%) pts COVID-19 was diagnosed and laboratory confirmed before hospitalization (hospitalized in 5.3±3.6 days after symptoms onset). 31 (22.3%) pts were diagnosed with COVID-19 upon admission, and 29 (20.9%) - during their stay in the hospital. 20 (15.6%) pts were vaccinated against COVID-19. The initial SpO2 level was 91.6±10.3%, while more than half of pts (53.2%) had SpO2<95% and almost every fourth (23.2%) patient had SpO2<90%. During the hospital period, 20 (14.4%) pts died. The mortality rate was 28.0% in pts with ADHF, 19.1% in pts with AMI and significantly less in pts hospitalized for unstable angina, hypertensive urgency or atrial fibrillation - 5.2% (p<0.05 in comparison with pts with AMI or ADHF). The main cause of death was the development of cardiopulmonary failure – 14 (70.0%) pts. 4 (20.0%) pts died from AMI complications, 1 - from pulmonary embolism and 1 - from acute ischemic stroke. Two critical periods of in-hospital mortality can be distinguished: 1 - the first two days of hospitalization (mainly complications of acute cardiovascular pathology and thrombotic events); 2 – from 7 to 10 days after hospitalization (development of multiple organ failure due to hypoxia and heart failure progression). The mortality rate of patients with ACP and COVID-19 was significantly higher than that of simultaneously hospitalized patients without comorbid respiratory infection (14.4% vs. 6.4%, p=0.012) and patients who were hospitalized before the pandemic (14.4% vs. 2.9%, p<0.001). Vaccinated patients were significantly less likely to develop acute kidney injury, acute hypoxic delirium, had higher average blood spO2, and less often required non-invasive ventilation. Only 1 vaccinated patient died from the development of cardiogenic shock against the background of anterior AMI and multivessel coronary artery disease (mortality – 15.7% in unvaccinated pts vs 5.0% in vaccinated, p=0.076). Co-infection with COVID-19 worsens treatment outcomes and in-hospital mortality of patients with ACP. Vaccination significantly reduces the likelihood of complications and tends to reduce mortality.